2013
DOI: 10.1007/s12088-013-0441-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel Class 1 Integrons in Multi-drug Resistant Isolates from Eastern China

Abstract: Integrons are mobile genetic elements able to capture, express and excise resistance genes, playing an important role in the spread of bacterial resistance. The present study was to investigate the occurrence and diversity of integrons in 120 clinical multi-drug resistant Gram-negative isolates from eastern China. Screening of integrons was performed by PCR and gene cassettes were further characterized by PCR-RFLP and sequencing. Class 1 integrons were detected in 70.8 % of isolates and no class 2 and class 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…While the prevalence of int2 gene is documented in some reports [ 24 , 27 ], none of P . aeruginosa strains in this study were found to carry int2 gene, which was in concordant to other previous reports [ 6 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…While the prevalence of int2 gene is documented in some reports [ 24 , 27 ], none of P . aeruginosa strains in this study were found to carry int2 gene, which was in concordant to other previous reports [ 6 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of int1 gene in clinical isolates of P . aeruginosa , is reported differently in similar investigations from Iran ranged from 43% to 56.3% [ 17 , 23 ], and around the world [ 6 , 15 , 24 ]. In mentioned reports and other documented studies, the prevalence is lower compared to the present study and this could be due to a trend of rapid increasing of integron positive rate among clinical isolates of P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, while the occurrence of int2 gene in Pseudomonas aeruginosa has been previously reported (Xu et al, 2009; Goudarzi et al, 2015), none of the Pseudomonas strains included in this study were found to carry the int2 gene, which was in concordant to other reports of P. aeruginosa from clinical settings (Rossolini and Mantengoli, 2005; Sun et al, 2014; Khosravi et al, 2017). It must be noted that class 2 integrons are not usually detected in Pseudomonas strains from environmental sources, being most commonly associated with members of the family Enterobacteriaceae, such as E. coli and Salmonella enterica (Ahmed et al, 2005; Antunes et al, 2006; Cocchi et al, 2007; Essen-Zandbergen et al, 2007; Laroche et al, 2009; Ozgumus et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Six studies claimed they found the novel gene cassette array which was not found in any species previously [ 4 , 7 – 8 , 20 , 33 , 54 ] . All the novel gene cassette arrays were detected from Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%